HABITAT AND SPECIES SEGREGATION OF STRIGIFORMES IN THE BRAZILIAN ATLANTIC FOREST - Martos-Martins, Rafael [UNESP]; Donatelli, Reginaldo José [UNESP] (Aves Argentinas / Asociacion Ornitologica del Plata, 2023)
The order Strigiformes contains approximately 250 owl species distributed worldwide, and the majority of them live in forests. Although basic information is available on many owls, few have been studied in-depth; consequently, little is known about the role of vegetation in their lives. This study aimed to investigate Strigiformes in a fragment of the Atlantic Forest using point count surveys conducted from January 2018 to December 2019. Twelve points were sampled for 30 min/month, totaling 144 h. Data on vegetation structure were collected for analysis. The numbers of individuals and species were then estimated. Twenty-six individuals of four species were recorded: 12 Strix virgata, 6 Pulsatrix koeniswaldiana, 5 Megascops atricapilla, and 3 Megascops choliba. Strix virgata was associated with sites with typical mature forest characteristics, although it tolerated variation in some parameters (e.g., average canopy height). Pulsatrix koeniswaldiana was a generalist in terms of habitat characteristics, even when using edge areas. Megascops choliba was scarce within the sampled area and seemed to avoid mature forest. Megascops atricapilla occurred from sites with a lower canopy to more mature forest areas. Altogether, this study highlighted the importance of conserving forest fragments in the Atlantic Forest, which harbors considerable biodiversity, especially of owls.
HÁBITAT Y SEGREGACIÓN DE ESPECIES DE STRIGIFORMES EN EL BOSQUE ATLÁNTICO BRASILEÑO
Keywords: biodiversity conservation; birds; Brazilian Atlantic rainforest; species segregation